Improving Passing Learning Outcomes for Mentally Disabled Children through Command Learning Methods in Football Games - Jumarel, Nuryadi (International Journal of Pedagogy, 2023)
The low learning outcomes for passing in class body weight position is not forward. The aim of this research is to find out whether the use of the command learning method can improve the learning outcomes of basic passing techniques for mentally retarded children. The population and sample in this study were students with intellectual disabilities in class X SMALB, totaling 4 students. This research is Classroom Action Research. The data collection techniques used were performance tests, student and teacher observation sheets. Data were analyzed by exposure between cycles. Based on the initial data results, the average student score was 65.25. Learning improvements in cycle I, the average student score rose to 75.5 or 10.25%. Learning improvements in cycle II saw an increase in the average student score by 81 or an increase of 5.5%. The research results in cycle II showed that there was a significant increase in classical completeness compared to cycle I with scores having reached the Minimum Completeness Criteria (KKM 75).